Comparison of Structural, Physicochemical, and Functional Properties of Blueberry Residue Dietary Fiber Extracted by Wet Ball Milling and Cross-Linking Methods - Guihun Jiang; Kashif Ameer; Karna Ramachandraiah; Xiaoyu Feng; Xiaolu Jin; Qiaolin Tan; Xianfeng Huang (Foods)
This study evaluated the structural, physicochemical, and functional characteristics of blueberry residue dietary fiber (DF) extracted by wet ball milling (WB) and cross-linking (C) treatments. The particle size of WB-DF showed a significant decreasing trend (p ≤ 0.05) compared to that of C-DF and blueberry residue. Scanning electron microscopy (SEM) demonstrated that WB treatment unfolded the flaky structure of DF and caused more pores to occur. The results showed that the modifications of WB increased the release of active groups and enhanced the hydration and adsorption capacities. X-ray diffraction (XRD) analysis showed the highest crystallinity observed for C-DF, resulting in the increased thermal stability of C-DF. The molar ratios of monosaccharides were also influenced by different modification techniques. In addition, WB-DF showed the lowest ζ-potential and highest viscosity among all samples. Conclusively, DF extracted by WB treatment exhibited remarkable application potential in the functional food industry.